DAMPAK KEBERADAAN PERKEBUNAN SAWIT PT. MITRA ANEKA REZEKI TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT SEKITAR HUTAN LINDUNG DI DESA SUNGAI DERAS KECAMATAN TELUK PAKEDAI - Ramadania, Fency; Muin, Sudirman; Herawatiningsih, Ratna (Universitas Tanjungpura, 2016)
The existence of oil palm plantations of Forest Protected Areas in Sungai Deras village has been around a long and until now has not known the public perception in Sungai Deras village of the impact of the presence of oil palm plantations on the socioeconomic conditions of society. Palm plantations are very difficult to stop because it is the main livelihood of the people. This research was conducted by the method of sampling respondents using purposive sampling. The primary date obtained through interviews using a list of questions that had been prepared directly in the field with the number of respondents in this study 88 respondents are heads of households and a minimum age of 18-45 years to live at least 5 years by means of analysis correlates simple method of Coefficient Correlation Bivariate Pearson (product moment personal). Characteristics palm plantation community dominated by adulthood, the oil workers as a livelihood, and education level were not completed primary schools. The impact of oil palm plantations on the socioeconomic conditions including being in the oil palm plantations and palm oil plantations impact on the environment, including moderate physical condition. This is because the revenue from oil palm plantations to meet their needs. Age level, significant related education and income, family burden and dependence on forests is not significantly related to the social impact of oil palm plantations on the economy. Level of age, education, income, family burden and dependence on forests is not significantly related to the impact of oil palm plantations on the physical condition of the environment. Keywoard : Community perception, the impact of oil palm plantations, the socio economic